Reception in Lithuania of Historical Culture Project (About a Defence of Rūta Šermukšnytė Doctoral Thesis "Actualization of Lithuanian history in documentary cinema and television (1988-2005)") - Žiemelis, Darius (Lietuvos istorijos studijos, 2006)
-
Keywords: -